Associations Among Infant Iron Deficiency, Childhood Emotion and Attention Regulation, and Adolescent Problem Behaviors. Issue 2 (23rd February 2017) - East, Patricia; Delker, Erin; Lozoff, Betsy; Delva, Jorge; Castillo, Marcela; Gahagan, Sheila
Abstract : This study examined whether iron deficiency (ID) in infancy contributes to problem behaviors in adolescence through its influence on poor regulatory abilities in childhood. Chilean infants ( N = 1, 116) were studied when there was no national program for iron fortification (1991–1996), resulting in high rates of ID (28%) and iron‐deficiency anemia (IDA, 17%). Infants (54% male) were studied at childhood ( M age = 10 years) and adolescence ( M age = 14 years). IDA in infancy was related to excessive alcohol use and risky sexual behavior in adolescence through its effect on poor emotion regulation in childhood. Attentional control deficits at age 10 were also related to both infant IDA and heightened risk taking in adolescence. Findings elucidate how poor childhood regulatory abilities associated with infant IDA compromise adjustment in adolescence.